Odpowiedzi

2009-11-06T10:55:26+01:00
Y=[x+1]²-4 y=-x-3 x²+2x+1-4=-x-3 x²+2x+1-4+x+3=0 x²+3x=0 Δ=b²-4ac=9-12=-3 Δ<0 →układ równań nie ma rozwiązania pozdrawiam
2009-11-06T11:01:05+01:00
Y=(x+1)²-4
y=-x-3

y=x²+2*x*1+1²-4
x=-3-y

y=(-3-y)²+2*(-3-y)-3
x=-3-y

y=-3²-2*(-3)*y*y²-6-2y-3
x=-3-y

y=9+6y*y²-6-2y-3
x=-3-y

y=4y*y²
x=-3-y

y nie może równać się 4y*y², układ równań sprzeczny.
2009-11-06T11:59:25+01:00
Y=(x+1)²-4
y=-x-3

y=x²+2x+1-4
y=-x-3

y=x²+2x+1-4
x=-3-y

y=(-3-y)²+2(-3-y)+1-4
x=-3-y

y=9-6y+y²-6-2y+1-4
x=-3-y

y+6y-y²+2y=-4+1-6+9
x=-3-y

9y-y²=0
x=-3-y

y=0
x=-3-0

y=0
x=-3